MyJapfa Application Information System Audit Using Cobit 2019 Framework Subdomain DSS02 - Muchamad Agung Luxvacry; Arny Lattu; Hendri Ekasatria (Teknika, 2025)
The effective implementation of Information Technology (IT) governance plays a crucial role in enhancing operational efficiency, particularly in the agribusiness industry, which is increasingly reliant on digital systems. PT Japfa Comfeed Indonesia Tbk Unit Kalapanunggal 2 utilizes the MyJapfa application to manage service requests and incident resolution as part of its IT service operations.This study aims to evaluate the capability level of the MyJapfa application using the COBIT 2019 framework, specifically focusing on the DSS02 subdomain—Managed Service Requests and Incidents. COBIT 2019 is a globally recognized IT governance model that ensures IT processes are aligned with organizational goals, making it highly relevant for agribusiness companies seeking consistency, compliance, and adaptability. The research methodology includes interviews, direct observations, and document analysis to measure IT process maturity. The findings reveal that the MyJapfa system currently operates at Capability Level 4 (Predictable Process), indicating consistent and measurable practices. However, several issues were identified, such as insufficient incident classification, lack of automated monitoring, and limited documentation of incident resolution. Recommendations include enhancing automation, formalizing classification schemes, integrating ERP systems, and conducting regular audits. These efforts are expected to strengthen IT governance and contribute to the digital transformation of the agribusiness sector.